Pressure dependence of the dissociation of acetic, benzoic, mandelic and succinic acids at 298.15 K - Kumar, Anil (Thermochimica Acta, 2005)
Dissociation constants for acetic, benzoic, mandelic and succinic acids have been measured at 298.15 K as a function of pressure up to 138.8 MPa. The spectrophotometric technique using Bromocresol Green as the optical indicator was employed up to ionic strength of 0.03 mol kg(-1) in aqueous solution. Thermodynamic dissociation constants were calculated with the Davies activity coefficient equation. The pressure dependences of the ionization constants for the weak acids can be described by the equation of Lown, Thirsk and Wynne-Jones, application of which leads to accurate partial molal volume change on ionization, Delta(V) over bar (o) and compressibility change, Delta(K) over bar (o) at 0.1 MPa. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Acetic acid; benzoic acid; dissociation constants; high pressure; mandelic acid; succinic acid

Vapour phase oxidation of acetophenone to benzoic acid over binary oxides of V and Mo - Chumbhale, Vilas R.; Paradhy, S. A.; Anilkumar, Mettu; Kadam, S. T.; Bokade, Vijay V. (Chemical Engineering Research and Design, 2005)
Test data for catalytic oxidation of acetophenone into benzoic acid performed at bench scale with V2O5-MoO3 catalyst in a continuous downflow metal reactor are presented. The process parameters such as temperature and flow rate influence the product distribution. The P2O5, B2O3 and Na2O when used as dopant on V2O5-MoO3 catalyst showed marked influence on activity and selectivity. An acidic catalyst like V2O5-MoO3-P2O5 favours formation of benzoic acid while a basic catalyst like V2O5-MoO3-Na2O favours formation of benzaldehyde. The addition of Na2O into V2O5-MoO3 binary oxides formed new phases (NaVMoO6 and Na2V2Mo3O15), which increased Arrhenius activation energy from 18.24 to 31.35 kcal mol(-1).
Keywords: acetophenone; activity; benzoic acid; carbon oxides; oxidation of acetophenone; selectivity